Impact of the COVID-19 pandemic on survival of MSMEs in Zimbabwe - Kapesa, Tonderai; Nyagadza, Brighton; Mugano, Gift; Cheza, Alexander (International Journal of Financial, Accounting, and Management, 2023)
Purpose: This study aimed to assess the impact of COVID-19 and its associated lockdowns on the survival of micro, small, and medium enterprises (MSMEs) in Zimbabwe, where more than 60 percent of economic activity is conducted through MSMEs. Research methodology: This study was conducted through an online survey of 447 individuals representing MSMEs operating in Zimbabwe. Data were analyzed using the statistical package for social sciences (SPSS), guided by a binary logistic regression model, to assess the impact of COVID-19 on the survival of MSMEs in Zimbabwe. Results: The model showed that the independent variables had a significant impact on the survival of MSMEs, with an overall accuracy of 87.9% in predicting the effects of COVID-19 on the survival of MSMEs. The study concluded that many MSMEs in Zimbabwe were negatively affected by the COVID-19 lockdown, except for those in strategic economic sectors that were not required to close their operations during the lockdowns. Limitations: The major limitation of the study was the low response rate of MSMEs operators from remote areas who could not respond to the online survey because of the nature of their business operations, which is survivalistic in nature and would not afford them time to respond to the survey. Contribution: The study recommends the provision of financial rescue packages by the government, development partners, civic organizations, and government policy realignment to ensure that MSMEs are resuscitated after lockdowns have been lifted. Novelty: This study contributes to the post-COVID-19 discourse, as global economies are rebuilding after the relaxation of COVID-19 related business operation restrictions. This is more important for developing countries that are most negatively affected and require their economies to recover from COVID-19 related economic depression.